2001
DOI: 10.1089/109493101753376678
|View full text |Cite
|
Sign up to set email alerts
|

The Functions of Internet Use and Their Social and Psychological Consequences

Abstract: Although the Internet has spawned significant changes in communication and interpersonal behavior, the data concerning the social and psychological effects of its use are equivocal. Drawing on the uses and gratifications model of communications media, it was hypothesized that the social and psychological effects of Internet use depend primarily on the user's reasons and goals for using the technology. That is, the Internet's social and psychological effects depend upon the functions it serves for users. A theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
162
2
15

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(194 citation statements)
references
References 25 publications
6
162
2
15
Order By: Relevance
“…About half of the total variance in the Internet use is accounted for by two major motives -socio-affective regulation and good-andinformation acquisition. Internet use driven by socioaffective regulation motives negatively influences psychological well-being through reducing off-line social integration, whilst the reverse is true for good-and-information acquisition [6]. Using a sample of 500 children, Jackson et al [7] similarly demonstrated the detrimental effects of Internet use for communication purposes (all other uses were associated with greater psychological well-being).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…About half of the total variance in the Internet use is accounted for by two major motives -socio-affective regulation and good-andinformation acquisition. Internet use driven by socioaffective regulation motives negatively influences psychological well-being through reducing off-line social integration, whilst the reverse is true for good-and-information acquisition [6]. Using a sample of 500 children, Jackson et al [7] similarly demonstrated the detrimental effects of Internet use for communication purposes (all other uses were associated with greater psychological well-being).…”
Section: Introductionmentioning
confidence: 99%
“…To date, few studies have looked at 'ordinary' community dwellers or relied on probability sampling techniques in their selection of participants. Valkenburg and Peter [3] point out that the vast majority of reported studies used depression and loneliness measures as indicators of well-being, with only a few notable exceptions published to date [2,3,6,18,22]. They also suggest that inconsistencies in findings with regard to Internet use and well-being may be explained by treating Internet use as a unitary construct.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is known that various pathologies occur due to the insensible, in other words excessive, use of these social media tools (Kuss & Griffiths, 2011). Studies have emphasized that individuals who spend their time online are lonelier in their real life (Shaw & Gant, 2002;Turkmen, 2016;Weiser, 2001). LaRose, Eastin, and Gregg (2001) define virtual environment as being alone in the crowd.…”
Section: Introductionmentioning
confidence: 99%
“…A review on literature reveals that at least two theoretical perspectives exist regarding the effects of online communication on users' well-being: the displacement hypothesis and the augmentation hypothesis. The displacement hypothesis asserts that time spent using a given medium replaces that spent using other mediators (Nie, Hillygus, & Erbring, 2002;Shklovski, Kraut, & Rainie, 2004), implying that online communication users have spent time in online settings rather than offline situations and then their subjective well-being would be harmed (Morgan & Cotten, 2003;Nie, Hillygus, & Erbring, 2002;Nie, 2001;Weiser, 2001). For example, Kraut et al (1998) suggested that online communication users substitute weak ties for strong ones, implying that Internet motivates adolescents to form online contacts with strangers, instead of maintaining relationships with existing friends.…”
Section: Introductionmentioning
confidence: 99%